Learning from feces: a case study teaching microbiome analysis - Thomas, Aeisha; Davis, Debra; Faue, Jasmine; Kicker, Sierra (Frontiers in Education, 2025)
Microbiome data is increasingly important in health and environmental research. This data can be used to teach students both microbiology content as well as data science competencies. A narrative case study, Learning from Feces: the Effects of Antibiotics on Gut microbiomes, was developed where publicly available human gut microbiome data from infants treated with antibiotics is analyzed using the student-accessible, user-friendly DNA Subway Purple line. Students, through this case study, learn about microbiome analysis including how to choose samples and process sequence data through a pipeline and finally interpret and explain the biological relevance of this data. This case study was successfully implemented in Microbiology courses for both majors and non-majors as a multi-step module on microbiomes. This manuscript presents the case development process that includes undergraduate authors, learning objectives, teaching materials and the results of implementation. Reflections on the implementation in two different courses are shared with notes for future users. It is hoped that this case will be effective in student learning and helpful for other instructors, especially those with limited data science training and the time and financial resources required for a full wet lab.